Determinants of firms' efficiency: Do innovations and finance constraints matter?the case of European SMEs - Graziella Bonanno; Annalisa Ferrando; Stefania Rossi (European Central Bank (ECB), 2020)
This paper aims at investigating the relationship between firms' profit efficiency, access to finance and innovation activities. We enrich our understanding on firms' performance by adopting the stochastic frontier approach (SFA), which allows us to estimate profit functions and to obtain efficiency scores for a large sample of European firms. We pioneer the use of a novel dataset that merges survey-based data derived from the ECB Survey on access to finance for enterprises (SAFE) with balance sheet information. Our evidence documents that credit constrained firms display an incentive to improve their efficiency in order to increase profitability. Among firms that have embarked in product innovation, those in the industry and high-tech sectors see their effort translated in higher profit efficiency. From a policy perspective, our results could help to better understand the link between innovation, financial constraints and efficiency, which goes beyond the idea that easier access to finance is the panacea to get higher profit efficiency.
Keywords: D22; D24; L23; O31; C33; 330; Stochastic Frontier Approach; access to finance; innovation; survey data